Application of Project-Based Learning to Improve the 4C Abilities (Critical Thinking, Creativity, Collaboration, and Communication) of Children Aged 5-6 Years - Tumbel, Meiske Esther (JR Education, 2024)
This research aims to improve the 4C (Critical Thinking, Creativity, Collaboration, and Communication) abilities of children aged 5-6 years by using the Project Based Learning (PjBL) learning model. This research uses a type of classroom action research using the Kemmis and Mc Taggart model through 4 stages, namely: 1) planning, 2) Action, 3) Observation, and 4) Reflection. The subjects in this research were children aged 5-6 years at GMIM Sion Tomohon Kindergarten with a total of 23 children. The data collection technique uses observation and non-test techniques which are used to measure the creativity of children aged 5-6 years, namely batik work using natural papaya leaves using the ecoprint technique. Data collection instruments use observation assessments (attitude assessments), work skills assessments work results assessment instruments, as well as questionnaires for assessing children's developmental achievements. The data analysis used in this research is quantitative and qualitative, namely simple descriptive statistics, the data reduction process, data presentation, and conclusion are carried out in the qualitative analysis process. The research results show that there is an increase in the 4C (Critical Thinking, Creativity, Collaboration, and Communication) abilities of children aged 5-6 years through the Project Based Learning (PjBL) learning model. This is proven by the activities of teachers and children who support the 4C indicators.